Carbon Dioxide Angiography: Scientific Principles and Practice - Cho, Kyung Jae (Vasc Specialist Int, 2015)
Carbon dioxide (CO(2)) is a colorless, odorless gas which occurs naturally in the atmosphere and human body. With the advent of digital subtraction angiography, the gas has been used as a safe and useful alternative contrast agent in both arteriography and venography. Because of its lack of renal toxicity and allergic potential, CO(2) is a preferred contrast agent in patients with renal failure or contrast allergy, and particularly in patients who require large volumes of contrast medium for complex endovascular procedures. Understanding of the unique physical properties of CO(2) (high solubility, low viscosity, buoyancy, and compressibility) is essential in obtaining a successful CO(2) angiogram and in guiding endovascular intervention. Unlike iodinated contrast material, CO(2) displaces the blood and produces a negative contrast for digital subtraction imaging. Indications for use of CO(2) as a contrast agent include: aortography and runoff, detection of bleeding, renal transplant arteriography, portal vein visualization with wedged hepatic venous injection, venography, arterial and venous interventions, and endovascular aneurysm repair. CO(2) should not be used in the thoracic aorta, the coronary artery, and cerebral circulation. Exploitation of CO(2) properties, avoidance of air contamination and facile catheterization technique are important to the safe and effective performance of CO(2) angiography and CO(2)-guided endovascular intervention.